2008
DOI: 10.1007/s12031-008-9114-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Proteomic Analyses of Mouse Cerebellum Reveals Alterations in RasGRF1 Expression Following In Vivo Chronic Treatment with Delta 9-Tetrahydrocannabinol

Abstract: We have applied transcriptomic and proteomic techniques to identify changes in the RNA and the protein levels in the mouse cerebellum after chronic treatment with Delta(9)-tetrahydrocannabinol (THC). Among approximately 14,000 transcripts in a mouse cDNA microarray library, we found 11 genes with altered expression. RasGRF1, a neuron-specific Ras guanine nucleotide exchange factor, showed a reduction both at the RNA and protein levels with a specific decrease of the protein pool associated to cell membranes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
6
25
0
2
Order By: Relevance
“…This is the first proteomic approach to the understanding of AEA pro-apoptotic activity. By the way, the first ever proteomic analysis on the effects of the cannabis-derived ⌬ 9 -tetrahydrocannabinol in chronic users (45), and in mouse cerebellum (46), appeared during the preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first proteomic approach to the understanding of AEA pro-apoptotic activity. By the way, the first ever proteomic analysis on the effects of the cannabis-derived ⌬ 9 -tetrahydrocannabinol in chronic users (45), and in mouse cerebellum (46), appeared during the preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…Of these proteins, ten were suppressed by THC and only one was induced, which might indicate a reduced synaptic efficiency in the PFC caused by THC treatment. Via proteomics analysis, Colombo et al [49] identified 24 unique differentially expressed proteins in the cerebellum of chronically THC-treated mice. Among these proteins, several alpha and beta subunits of guanine nucleotidebinding proteins, calcium-binding proteins (calretinin and hippocalcin-like protein 1), and dynamin-1 had induced expression.…”
Section: Marijuanamentioning
confidence: 99%
“…These data indicate that both CB subtypes were functional to a similar extent in human NHEM cells (Table 1). However, some discrepancies were observed between the activity and mRNA expression of AEA-and 2-AG-metabolizing enzymes, a finding that is not unprecedented for ECS elements (35,44). Overall, the present data demonstrate that primary human melanocytes have a complete and fully functional ECS.…”
Section: Resultsmentioning
confidence: 47%
“…Overall, the present data demonstrate that primary human melanocytes have a complete and fully functional ECS. Induction of Apoptosis-AEA at micromolar concentrations has been shown to trigger apoptosis in different cell types (34,44,45). Here we treated NHEM cells for 24 h with different amounts of mAEA, a non-hydrolyzable analog that binds the same targets and with the same affinity as AEA (3) and shows the same functional effects as the natural compound (3,4).…”
Section: Resultsmentioning
confidence: 99%